PERANCANGAN SISTEM PENGUJIAN FUNGSIONALITAS UNTUK MODUL CONTROLLER LAMPU HEMAT ENERGI - Sayyidhatus Az-Zahra; Ratna Ika Putri; Fitri (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
A testing device is required by the industry to ensure product quality through accurate and reliable testing of critical components in energy-saving lamp products. This research method includes the design phase of the testing device and the development of a measurement circuit focused on voltage, current, and power parameters in the energy-saving lamp controller module. The design of the electronic system for voltage and current sensors involves the use of voltage divider circuits, shunt resistors, and the ADS1115 component as an analog-to-digital converter (ADC). Additionally, optocouplers and relays are used as part of the switching and circuit protection system. The 24-volt voltage sensor is designed to measure a voltage range of 17 to 24 volts, the 8-volt voltage sensor to measure a range of 4 to 8,4 volts, and the current sensor to measure a current range of 150 mA to 470 mA. Based on testing results, the 24-volt voltage sensor showed an average error of 0,009%, the 8-volt voltage sensor 0,008%, and the current sensor 0,07%. Therefore, this testing device can be utilized to improve the efficiency of the production process and ensure the consistent quality of the energy-saving lamp controller module.